Improving risk analysis - Cox, Jr., Louis Anthony (International Series in Operations Research & Management Science, 2013)
Improving Risk Analysis discusses and illustrates practical methods for assessing, communicating, and managing uncertain risks when the probabilities of consequences caused by alternative actions cannot be quantified with useful confidence, accuracy, and precision. This monograph demonstrates how to avoid these pitfalls by using improved techniques of risk analysis. Through these improved techniques of risk analysis, readers will better understand uncertain risks and be able to make more effective decisions about how to manage them.  The book is divided into three parts. Parts 1 and 2 explore the key principles on how high-quality risk analysis can greatly improve the clarity and effectiveness of decisions when the consequences of different choices are uncertain. Part 3 shows in greater detail how these introduced methods can be applied to health effects of air pollution, with emphasis on understanding and modeling causal relations between exposures and responses based on realistically limited and imperfect data. Throughout the book, real-world examples and case studies drawn from health, safety, environmental, and terrorism risk analysis are used and illustrate the practical application of techniques for improving risk analysis.